A Sufi Interpretation of Sleep Paralysis: Al-Ghazali’s Perspective on Psychological and Spiritual Wellbeing - Adawiyah, Robiatul; Limas Dodi (Faculty of Ushuluddin and Philosophy, 2024)
Sleep is a state of total rest for the human body and mind, although vital organs remain active. One sleep disorder that has attracted attention is sleep paralysis, which in Indonesia is often associated with cultural beliefs such as the phenomenon of “ketindihan.” This study aims to examine sleep paralysis (ketindihan) from a Sufi perspective, specifically the thought of Imam al-Ghazālī, using a descriptive qualitative method based on a literature review. Based on an analysis of al-Ghazālī’s works, sleep paralysis is understood as a manifestation of a person’s psychological condition, where the dominance of negative traits in the heart, such as worldly desires and immoral behavior, leads to nightmares or sleep disturbances. Al-Ghazālī emphasizes the importance of purifying the heart, cultivating remembrance of God (dhikr), and controlling desires to achieve inner peace and quality sleep. This study concludes that the Sufi understanding of sleep paralysis offers a more holistic alternative interpretation, promoting the integration of mental health, spirituality, and culture in addressing this phenomenon. These findings also enrich the interdisciplinary body of thought between psychology, Sufism, and cultural studies.